The Influence of Metaphor as Flouting Maxim in the Novel The Fault in Our Stars by John Green - Dwi Husna; Jepri; Muhammad Adam (Prologue: Journal on Language and Literature, 2022)
The scope of the study is the limitation of the focus of the research. This research is focused on the metaphor found in flouting maxims and the way metaphor influences the emotion of characters in the novel The Fault in Our Stars. There are some aspects pragmatics that influenced human language. The researcher tries to find the implied meaning by analyzing the flouting maxim in the novel The Fault in Our Stars by John Green. The type of research is descriptive qualitative study. In this research, the source of primary data is derived from a novel entitled The Fault in Our Stars by John Green was published in 2012. In this research, the researcher analyses implicature in the novel, such as words, clauses, sentences, and conversations between characters, and flouting maxims. Identifying and selecting the data based on the types of metaphor and flouting maxims. Findings of this research are 20 excerpts metaphor in floating maxim. They are 8 excerpts categorized in structural metaphor, 9 excerpts categorized in ontology metaphor, and 3 excerpts categorized in orientational metaphor. These metaphors are found from 11 flouting maxim of manner, 4 flouting maxim of quality and 5 flouting maxim of quantity.